An Attempt at Matching Waking Events Into Dream Reports by Independent Judges - Wang, Jia Xi; Shen, He Yong (Frontiers in Psychology, 2018)
Correlations between memories and dreaming has typically been studied by linking conscious experiences and dream reports, which has illustrated that dreaming reflects waking life events, thoughts, and emotions. As some research suggests that sleep has a function of memory consolidation, and dreams reflect this, researching this relationship further may uncover more useful insights. However, most related research has been conducted using the self-report method which asks participants to judge the relationship between their own conscious experiences and dreams. This method may cause errors when the research purpose is to make comparisons between different groups, because individual differences cannot be balanced out when the results are compared among groups. Based on a knowledge of metaphors and symbols, we developed two operationalized definitions for independent judges to match conscious experiences and dreams, the descriptive incorporation and the metaphorical incorporation, and tested their reliability for the matching purpose. Two independent judges were asked to complete a linking task for 212 paired events-dreams. Results showed almost half dreams can be matched by independent judges, and the independent-judge method could provide similar proportions for the linking task, when compared with the self-report method.